Front view of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The west-facing Shiva temple now consists of a garbhagriha (sanctum sanctorum) and an antarala (vestibule or antechamber), with the mandapa (pillared hall) having fallen into disrepair. The upper part of the shikhara (superstructure) has been affected by damage. Stylistically, the temple dates back to the twelfth century CE.